Meta-Analysis of the Influence of the STEM-Integrated Learning Model on Science Learning on 21st Century Skills - Asrizal; Usmeldi; Riza Azriyanti (Jurnal Penelitian Pendidikan IPA, 2023)
One of the skills that students must have 21st century skills. In order for students to understand and master the skills of learning materials, especially science learning, it is necessary to apply the STEM integrated learning model. Meta-analytic research is needed on the effect of the STEM integrated learning model on science learning on 21st century skills based on different previous research findings. The purpose of this research is to see how much influence the STEM integrated learning model has on science learning on 21st century skills in terms of educational level, learning models, and types of 21st century skills. The research method used is a meta-analysis of 22 articles in national and international journals. Coding is a data collection technique, and for effect size analysis it is used for data analysis techniques. The research results obtained, namely with variations in educational levels, learning models, and 21st century skills, state that the application of STEM integrated learning models in science learning has a high influence on 21st century skills. The conclusion from this meta-analysis research is that there is a high influence from the application of the model STEM integrated learning in science learning towards 21st century skills.